A formação de professores para os estudos do meio - Dias, José Roberto Gonçalves (2015)
Environmental Studies are scientific proposals for pedagogical work which comprehend an initial planning, getting out of the classroom environment, exploration and evaluation of results. It has been used throughout the history of education as an effective learning activity, for students and for teachers professional development. However, it is not always based on principles of learning and appropriately guided by its proponents, according to the school reality features. Therefore, this research has the objective: to prepare a proposal for training for elementary and high school teachers, to carry on in a qualified way Environmental studies projects, considering the teachers formation needs and the students learning objectives. We also aim to specific objectives: to characterize the environmental studies; list the students' learning possibilities to be performed in the context of environmental studies; identify teachers needs to work on environmental studies; and draft a teachers training course for environmental studies. This qualitative research is based on the literature review and documental analysis of previous experiences, which supported the preparation to a proposal for continuing education for elementary and high school teachers, which values their personal experience as teachers and the educational context in which they work, considering the pedagogical possibilities offered by this important teaching procedure